Genomic Study of High-Risk Clones of Enterobacter hormaechei Collected from Tertiary Hospitals in the United Arab Emirates - Akela Ghazawi; Febin Anes; Shaimaa Mouftah; Mohammed Elbediwi; Awase Baig; Muna Alketbi; Fatema Almazrouei; Mariam Alhashmi; Norah Alzarooni; Ashrat Manzoor; Ihab Habib; Nikolaos Strepis; et al. (MDPI AG, 2024)
Enterobacter hormaechei has emerged as a significant pathogen within healthcare settings due to its ability to develop multidrug resistance (MDR) and survive in hospital environments. This study presents a genome-based analysis of carbapenem-resistant Enterobacter hormaechei isolates from two major hospitals in the United Arab Emirates. Eight isolates were subjected to whole-genome sequencing (WGS), revealing extensive resistance profiles including the blaNDM-1, blaOXA-48, and blaVIM-4 genes. Notably, one isolate belonging to ST171 harbored dual carbapenemase genes, while five isolates exhibited colistin resistance without mcr genes. The presence of the type VI secretion system (T6SS), various adhesins, and virulence genes contributes to the virulence and competitive advantage of the pathogen. Additionally, our isolates (87.5%) possessed ampC β-lactamase genes, predominantly blaACT genes. The genomic context of blaNDM-1, surrounded by other resistance genes and mobile genetic elements, highlights the role of horizontal gene transfer (HGT) in the spread of resistance. Our findings highlight the need for rigorous surveillance, strategic antibiotic stewardship, and hospital-based WGS to manage and mitigate the spread of these highly resistant and virulent pathogens. Accurate identification and monitoring of Enterobacter cloacae complex (ECC) species and their resistance mechanisms are crucial for effective infection control and treatment strategies.